Laguerre polynomial excited coherent state: generation and nonclassical properties. (13th October 2017) - Ye, Wei; Zhou, Weidong; Zhang, Haoliang; Liu, Cunjin; Huang, Jiehui; Hu, Liyun
Abstract: We propose a theoretical protocol to generate a kind of non-Gaussian state—a Laguerre polynomial excited coherent state (LPECS) by exploiting a two-mode squeezing transformation and a conditional measurement with a coherent state input. Then we investigate the nonclassical features of the LPECS according to the Glauber–Sudarshan P ( α ) function, photon number distribution, Mandel's Q parameter, second-order correlation function, and squeezing properties as well as negative Wigner distribution. Our results show that the generated output state presents obvious nonclassical properties which can be modulated by a coherent amplitude, a squeezing parameter and a conditional measurement. In particular, the squeezing and negative Wigner function are clear.